Rape or Rapaciousness in Jan Cornelisz Vermeyen’s Tunis Tapestries? - Baskins, Cristelle (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2025)
Court artist Jan Cornelisz Vermeyen produced a set of cartoons for the Tunis tapestries commissioned by Mary of Hungary and woven in Brussels in c. 1546–54. Throughout the ten extant cartoons, women are subjected to violence, but they are also presented as economically valuable captives and slaves. In the sole surviving preparatory drawing, Vermeyen recorded more extreme physical depredation, with the corpse of a young, obese woman lying on her side with her garments pulled up to expose her pubic mound and her upper left arm sliced open in two places. The violated woman rendered the rapaciousness of soldiers an inescapable fact. In addition, viewers may have associated the victim with the North African practice of bride fattening. However, this disturbing figure was eliminated from the final tapestries. While we lack direct testimony about that decision, it may have been informed by a combination of sexual, ethnographic, and medical discourses.